Evaluation of the Service Performance of Soil–Bentonite Vertical Cut-Off Walls at Heavy Metal Contaminated Sites: A Review - Ke Wang; Yan Zhang (Applied Sciences)
Soil–bentonite (SB) vertical cut-off walls are widely utilized to mitigate the transport of soil contaminants in groundwater. Evaluating their long-term service performance is crucial for ensuring environmental safety and effective pollution control. The evaluation model for the long-term service performance of contaminant cut-off walls considers key processes such as convection, diffusion, dispersion, and adsorption. These processes are closely linked to the physicochemical properties of the cut-off walls, which are influenced by the surrounding complex environment, ultimately impacting their long-term performance. This study delves into the long-term service performance of SB vertical cut-off walls. It focuses on the key factors that influence this performance and the measures that can enhance it. Moreover, it offers a detailed analysis of how the performance of seepage cut-off walls in soil–bentonite materials evolves under various environmental influences. These influences include chemical exposure, freeze–thaw cycles, and dry–wet cycles. Additionally, it outlines existing service performance evaluation methods and identifies their shortcomings. By leveraging the advantages of in situ testing methods, this paper proposes the establishment of a comprehensive evaluation system for the service performance of vertical cut-off walls based on in situ test parameters. The proposed evaluation system aims to provide a scientific assessment of the long-term service performance of SB vertical cut-off walls.